Patterns of (Af)filiation in Recent Canadian Bildungsromane - Easton, Paul Lee (My University, 1986)
Recently much critical work has female Bildungsroman although, with relatively little has been done been some on done on the exceptions, the Canadian Bildungsroman , male or female. This study gathers twelve Canadian Bildungsromane , six by men, six by women, published since 1972. Using the the concepts of filiation and affiliation as theorized by Edward Said, it postulates that a "gender gap" does exist and can best be explained In these terms.
Keywords: English Language and Literature; English Language and Literature